13C NMR spectra of 9-methylcarbazoles and electron conductivity of the carbazole ring; Chemistry of Heterocyclic Compounds; Vol. 20, iss. 2 - Filimonov V. D. Viktor Dmitrievich; Filippova T. A.; Lopatinskii V. P.; Sukhoroslova M. M. (1984, 1984)
Title screen